Dihydropyridine-coumarin-based fluorescent probe for imaging nitric oxide in living cells. Issue 9 (5th August 2020) - Ma, Sufang; Sun, Xueyi; Yu, Qiang; Liu, Rui; Lu, Zhonglin; He, Lan
Abstract : A new fluorescent probe for nitric oxide (NO) was prepared, which shows great potential for understanding the biological roles of NO in vivo . Abstract : Nitric oxide (NO) is a messenger molecule in organisms, participating in the regulation of many biological processes. The abnormal expression of NO is often observed in a variety of diseases, including cerebral ischemia, atherosclerosis, and cancer. However, a suitable tool that can directly and sensitively detect NO in vitro and in vivo is important for understanding its various biological functions. In this report, a new fluorescent probe for nitric oxide, DHP-4, was prepared, based on dihydropyridine-coumarin. DHP-4 was able to greatly enhance the fluorescence of NO, but did not affect the fluorescence emissions of other reactive oxygen species and nitrogen species, demonstrating its highly selective and sensitive response to NO. The probe generated stable optical signals in a buffer solution at pH values ranging from 3 to 10. In addition, DHP-4 could detect NO directly, showed low cellular toxicity, and was successfully applied to determine NO in Raw 264.7 cells, indicating its great potential as a tool for investigating the biological roles of NO in vivo .